Report of Working Group on Irrigation Management Improvement Programme For the Formulation of Eighth Five Year Plan (1990-95) Set Up By Planning Commission Government of India - Planning Commission (Planning Commission, 1989)
Water is a critical input for agriculture production. the primary source of water is rainfall, which is subject to vagaries of monsoon, characterised by delay in onset, breaks during the monsoon and early withdrawals. In order to have insurance against crop failure and also raise agriculture production, irrigation facilities are a must in Indian conditions. Massive efforts have therefore been made in creation of irrigation facilities to raise agricultural production and alleviate the rural poverty. The irrigation potential has increased from 22.6 million ha. at the beginning of First Plan 1950-51 ) to 67.5 million ha. by the end of Sixth Plan the anticipated achievement for Seventh Plan is 10.3 million ha. which will bring the created potential from all sources to about 77.8 million ha. against the ultimate irrigation potential of 113 million ha. the food production has increased from 50 million tonnes in 1950-51 to about 150 million tones by the end of Sixth Plan. The total cultivated area of the country is about 180 million ha. ,of which, the area under food crops is about 130 million ha. Thus, the average food production per ha. is only 1.15 tonnes. Statistics of the food production separately for irrigated area is not available the gross area under irrigation by end of Sixth Plan was about 52 million ha. Taking a productivity of 0.6 tonnes per ha from dry land, the average productivity of irrigated agriculture is not more than 2 tonnes per ha. which is very low by any standards. The low productivity of irrigated agriculture has been described to faulty management of inputs.
Report of Working Group on Irrigation Management Improvement Programme For the Formulation of Eighth Five Year Plan (1990-95) Set Up By Planning Commission Government of India
Government of India